Split intransitivity in old Japanese - You, Z (2014)
According to the Unaccusative Hypothesis (Perlmutter 1978), intransitive verbs fall in two distinct classes: the unaccusatives (whose subjects originate as direct objects) and the unergatives (whose subjects originate as subjects). Although there are studies of split intransitivity in Modern Japanese and European languages, very few exist for earlier stages of Japanese. To fill in part of this gap, this thesis presents a comprehensive investigation of split intransitivity in Old Japanese (largely, 8th century Japanese). The descriptive and analytic work of this research is based on the newly developed ‘Oxford Corpus of Old Japanese’ (OCOJ). It consists of original and romanized Old Japanese texts, with a wide range of information including the original orthography, part-of-speech, morphology and syntactic constituency in the form of XML tags following TEI conventions. It is part of a larger collaborative research project: ‘Verb semantics and argument realization in pre-modern Japanese: A comprehensive study of the basic syntax of pre-modern Japanese’, in which my DPhil project is situated. As part of my DPhil project, I took part in the analysis and tagging of the OCOJ, in addition to contributing to translation. My original contribution to knowledge is a comprehensive investigation and in-depth analysis of the lexical-semantic aspects of split intransitivity in relation to its morpho-syntactic expressions in Old Japanese. This includes: exploring to what extent intransitive verbs could be classified as unaccusative and unergative, what factors are involved in the classification, how they interact, what are the possible ways of representation, and the theoretical implications it brings to linguistic theory in general. Syntactically, I looked into manifestations specific to Old Japanese (e.g. perfective auxiliary selection), and also examined to what extent diagnostics – which show split intransitivity in English, Italian and Modern Japanese (e.g. N+V compounding and resultative construction) – could be applied to Old Japanese. Semantically, I investigated various semantic factors and proposed basic and complex models of the interaction between intentionality and affectedness in Old Japanese. I also proposed a ‘complex format for representing simple event structures’ which enhances the understanding of semantic aspects of split intransitivity. As such, the results of my research not only contribute to a detailed understanding of Old Japanese verbs, but also have implications for linguistic theory in general.